Fire resistance of self-compacting geopolymer concrete (SCGC) - Ng, Kai Qi (Nanyang Technological University, 2021)
Self-compacting concrete (SCC) is a concrete material with high flowability which promotes ease of construction without mechanical vibration, and could achieve comparable or even better structural performance than conventional vibrated concrete. This is especially true in concrete structures with congested reinforcement. However, SCC contains higher proportions of fines and has impermeable microstructure which can cause explosive spalling after exposure to high temperature. Despite the efforts of using Polypropylene (PP) fibres to minimise spalling in SCC, the compressive strength of SCC deteriorates with increasing number of voids due to melting of PP fibres at elevated temperature. On the other hand, geopolymer is an innovative green construction material that displays potential in being an alternative binder to OPC, by providing promising results on structural performance and fire resistance on top of contributing to sustainability efforts. However, the intrinsic fire resistance of geopolymers starts to fail with addition of aggregates and aggregates are required in the mix proportion of SCC. As such, this study was conducted to test the suitability of developing self-compacting geopolymer concrete (SCGC) which uses geopolymer’s superior fire resistance properties to enhance thermal performance of SCC. Fly ash geopolymer with potassium-based alkaline activator, was used to study the effect of varying water content and addition of aggregates, on the fresh and mechanical properties of the concrete. Fresh concrete properties of fly ash SCGC were performed using slump-flow and J-ring test. Ambient and residual (850 ℃) compressive strength test results were recorded for fly ash geopolymers. For metakaolin geopolymer, mix design using potassium-based alkaline activator was experimented using fumed silica and potassium silicate solution. Comparison was also made between potassium-based and sodium-based alkaline activator. Ambient compressive strength test results were recorded for metakaolin geopolymers.